A global review of implementation of occupational safety and health management systems for the period 1970-2020 - Mandowa, Johanes; Matsa, Mark; Jerie, Steven (Taylor and Francis Ltd, 2022)
Objectives. Global awareness on occupational safety and health management systems (OSHMSs) has increased exponentially with time over the years. Evidence in the public domain shows there is still much skepticism and reluctance in implementing OSHMSs, particularly in least developed and developing countries. The primary objective of this theoretical review was to analyze available evidence of research gaps on OSHMS implementation globally over the period 1970-2020. Methods. The review adopted a descriptive mixed-methods design premised on its ability to provide a platform for data triangulation that is paramount in enhancing the authenticity of the review findings. Results. Many studies conducted on implementation of OSHMSs were bereft of examining the challenges of OSHMS implementation. The review further exposed some OSHMS implementation disparities existing between the developed and the developing world, hence a conclusion can be drawn that a 'one size fits all approach' to OSHMS implementation may not ideal for many workplaces. Conclusion. This review recommends contextualization of OSHMS implementation taking into consideration other differing environmental factors. Ultimately, propagation of further research will exude the challenges associated with implementation of OSHMSs and their causal factors, thereby providing the basis for establishment of problem-driven solutions to increase uptake of OSHMS in workplaces.